The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1093/bja/87.2.250
|View full text |Cite
|
Sign up to set email alerts
|

A reduction in Type and Screen: preoperative prediction of RBC transfusions in surgery procedures with intermediate transfusion risks †

Abstract: In many patients, a 'type and screen' procedure is routinely performed before surgery. However, most patients are not transfused after all. Can we predict, which surgical patients will and will not be transfused, to reduce the number of these investigations? We studied 1482 consecutive surgical patients with intermediate risk for transfusion. Multivariate logistic regression modelling and the area under the Receiver Operating Characteristic curve (ROC area) were used to quantify how well age, gender, surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…24 These data suggest that a perioperative bleeding event should not increase the risk of death unless the hemoglobin level goes below 80 g/L or perhaps 70 g/L. Finally, numerous investiga- tors have attempted to predict bleeding requiring perioperative blood transfusion in noncardiac surgery, [25][26][27][28][29][30][31] but those studies were small compared to our study, with samples ranging from 94 to 1875 patients, and were often limited to a single centre and type of surgery.…”
Section: Discussionmentioning
confidence: 70%
“…24 These data suggest that a perioperative bleeding event should not increase the risk of death unless the hemoglobin level goes below 80 g/L or perhaps 70 g/L. Finally, numerous investiga- tors have attempted to predict bleeding requiring perioperative blood transfusion in noncardiac surgery, [25][26][27][28][29][30][31] but those studies were small compared to our study, with samples ranging from 94 to 1875 patients, and were often limited to a single centre and type of surgery.…”
Section: Discussionmentioning
confidence: 70%
“…This example shows that a threshold of 10.0% would not match clinician decision-making, whereas a threshold of 5.0% would match decisions. The choice of 5.0% matches the criterion from van Klei et al 8,9 A criterion based on an incidence of transfusion (e.g., 5.0% or more) differs from one based on the mean units transfused for each procedure (i.e., the "transfusion index"). 4 -6,23,24 One of our objectives was to interpret use of the mean units transfused.…”
Section: Criteria For the Type And Screen Decisionmentioning
confidence: 92%
“…van Klei et al previously suggested that type and screen be performed for procedures with 5% or more incidence of transfusion with one or more units. 8,9 They showed that the criterion was suitable for multiple facilities, but studied only a few procedures, all with large numbers of cases. 8,9 Consider the decision whether to type and screen for "unilateral total hip replacement."…”
Section: Criteria For the Type And Screen Decisionmentioning
confidence: 99%
See 2 more Smart Citations